106k views
3 votes
Fill in the table using this function rule

y=-4x+3
x y
-1 =
0=
1=
2=

2 Answers

2 votes
This one isn't too hard, just plug in each value!

x = -1
y = -4(-1) + 3
y = 7

x = 0
y = -4(0) + 3
y = 3

x = 1
y = -4(1) + 3
y = -1

x = 2
y = -4(2) + 3
y = -5
User Skarllot
by
6.1k points
3 votes

Answer:

1st blank: 7

2nd blank: 3

3rd blank:
-1.

4th blank:
-5.

Explanation:

We have been given a function formula
y=-4x+3. We are asked to fill in the given table.

We will substitute the given x values in our given formula to solve for y as:


y=-4x+3


y=-4(-1)+3


y=4+3


y=7

1st blank: 7


y=-4x+3


y=-4(0)+3


y=0+3


y=3

2nd blank: 3


y=-4x+3


y=-4(1)+3


y=-4+3


y=-1

3rd blank:
-1


y=-4x+3


y=-4(2)+3


y=-8+3


y=-15

4th blank:
-5.

User Xonico
by
6.3k points